Screening for Postpartum Depression in Well-Baby Care Settings: A Systematic Review - van der Zee-van den Berg, Angarath I. (Matern Child Health J, 2016)
Introduction Postpartum depression (PPD) is a mental health problem frequently experienced by mothers in the first year postpartum. Early detection and treatment can help to reduce its negative effect on the development of the newborn child. Well-baby care (WBC) is a promising screening setting for early detection of PPD. This systematic review investigates the evidence of the effectiveness of screening for PPD in WBC settings regarding mother and child outcomes. Methods Three electronic databases were searched: SCOPUS, PsychINFO and CINAHL. Two reviewers independently performed the study selection. Data extraction was based on a predefined data extraction form. Results Six studies were included; a quality assessment rated two studies as strong and four as weak. Four studies measuring outcomes at process level showed improvement in detection, referral and/or treatment rates. Four studies, including the two strong ones, where screening and enhanced care were combined, showed improvements in the Edinburgh Postnatal Depression Scale scores of the mothers in the intervention groups. No improvements were reported on other outcomes at parent level or at child level. At child level, weight was the only outcome that was measured. Discussion This review provides limited yet positive evidence for the value of screening for PPD in a WBC setting. The outcomes are comparable with studies on screening for PPD in general. The evidence that we found is very promising but the small number of available studies shows a need for additional high-quality studies, to strengthen the evidence regarding the potential benefits of screening in a WBC setting.